Polarizing plate having retardation layer and picture display unit

The polarized plate with a phase difference layer, featuring a second adhesive layer with higher storage elasticity, addresses durability issues by suppressing dimensional changes and stress transmission, ensuring stable optical performance in image display devices.

JP2025016893APending Publication Date: 2025-02-05NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023119686
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Image display devices require polarized plates with phase difference layers that offer enhanced durability in harsh environments, as they are prone to dimensional changes due to stress, affecting optical characteristics.

Method used

A polarized plate with a phase difference layer comprising a first phase difference layer, a first adhesive layer, and a second phase difference layer, where the second adhesive layer has a storage elasticity greater than the first, ensuring the relationship G' AD2 > G' AD1, thereby suppressing dimensional changes and stress transmission to the phase difference layers.

Benefits of technology

The solution provides a polarized plate with improved durability and optical stability, maintaining performance under varying environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016893000001_ABST
    Figure 2025016893000001_ABST
Patent Text Reader

Abstract

To provide a polarizing plate having a retardation layer excellent in antireflection properties.SOLUTION: A polarizing plate having a retardation layer includes: a polarizing plate including a polarizer; a first retardation layer; a first adhesive layer; a second retardation layer; and a second adhesive layer, in this order. In the first retardation layer, refractive index characteristics exhibit a relation of nz>nx=ny. In the second retardation layer, refractive index characteristics exhibit a relation of nx>ny≥nz. The first retardation layer and the second retardation layer are made of a resin film. In the second adhesive layer, a storage elastic modulus G'AD2 is over 0.15 MPa.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a retardation layer-attached polarizing plate and an image display device. [Background technology]

[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices), are rapidly becoming widespread. In these image display devices, a polarizing plate with a retardation layer is used for the purpose of improving display characteristics and preventing reflection. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-66882 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, image display devices have been used in various environments, and durability in harsher environments is required. A main object of the present invention is to provide a retardation layer-attached polarizing plate having excellent durability. [Means for solving the problem]

[0005] 1. A polarizing plate with a retardation layer according to an embodiment of the present invention includes a polarizing plate including a polarizer, a first retardation layer, a first pressure-sensitive adhesive layer, a second retardation layer, and a second pressure-sensitive adhesive layer, in this order. The first retardation layer has a refractive index characteristic that satisfies the relationship nz>nx=ny, and the second retardation layer has a refractive index characteristic that satisfies the relationship nx>ny≧nz. The first retardation layer and the second retardation layer are resin films, and the second pressure-sensitive adhesive layer has a storage modulus G' AD2 exceeds 0.15 MPa. 2. The retardation layer-attached polarizing plate according to 1 above may have the polarizer and the first retardation layer laminated together via an adhesive layer. 3. In the retardation layer-attached polarizing plate according to 1 or 2 above, the second retardation layer may have Re(550) of 120 nm to 170 nm, and the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer may be 40° to 50° or 130° to 140°. 4. In the retardation layer-attached polarizing plate according to any one of the above 1 to 3, the second retardation layer may be a resin film containing a polycarbonate resin. 5. In the retardation layer-attached polarizing plate according to any one of the above 1 to 4, the storage modulus G' of the second pressure-sensitive adhesive layer is AD2 and the storage modulus G' of the first pressure-sensitive adhesive layer AD1 What is G' AD2 >G' AD1 The relationship may be satisfied. 6. The retardation layer-attached polarizing plate according to any one of 1 to 5 above may be used in an organic electroluminescence display device. 7. In another aspect of the present invention, there is provided an image display device, which comprises the retardation layer-attached polarizing plate according to any one of 1 to 6 above. 8. The image display device according to the above item 7 may be an organic electroluminescence display device. Effect of the Invention

[0006] According to the embodiment of the present invention, a retardation layer-attached polarizing plate having excellent durability is provided. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiments, but these are merely examples and do not limit the interpretation of the present invention. In this specification, (meth)acrylic refers to acrylic and / or methacrylic. In addition, in this specification, the symbol "to" indicating a numerical range includes the upper and lower numerical limits.

[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means 45° clockwise and 45° counterclockwise.

[0010] A. Polarizing plate with retardation layer The polarizing plate with a retardation layer according to an embodiment of the present invention comprises, in this order, a polarizing plate including a polarizer; a first retardation layer; a first adhesive layer; a second retardation layer; and a second adhesive layer. The first retardation layer exhibits a refractive index characteristic of nz>nx=ny, and the second retardation layer exhibits a refractive index characteristic of nx>ny≧nz. The first retardation layer and the second retardation layer are resin films. The storage modulus G' of the second adhesive layer AD2 The compressive strength exceeds 0.15 MPa. By adopting such a configuration, a retardation layer-attached polarizing plate having excellent durability can be provided.

[0011] A-1. Overall structure of polarizing plate with retardation layer FIG. 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. The retardation layer-attached polarizing plate 100 includes a polarizing plate 10 including a polarizer 11; a first retardation layer 21; a first adhesive layer 31; a second retardation layer 22; and a second adhesive layer 32, in this order. The polarizing plate 10 further includes a polarizer 11 and a protective layer 12 arranged on the side of the polarizer 11 opposite to the side on which the first retardation layer 21 is arranged. The polarizer 11 may further include a protective layer on the surface on which the protective layer 12 is not laminated (not shown). In the illustrated example, no protective layer is arranged between the polarizer 11 and the first retardation layer 21, and the first retardation layer 21 is arranged adjacent to the polarizer 11 via any suitable adhesive layer or adhesive layer. According to an embodiment of the present invention, even if the protective layer arranged on the first retardation layer side is omitted, the first retardation layer 21, which is a resin film, can function as a protective layer for the polarizer 11. Therefore, the durability of the retardation layer-attached polarizing plate 100 can be ensured. In addition, it can contribute to making the retardation layer-attached polarizing plate 100 thinner. The first retardation layer 21 has a refractive index characteristic that satisfies the relationship nz>nx=ny, and the second retardation layer 22 has a refractive index characteristic that satisfies the relationship nx>ny≧nz. The first retardation layer 21 and the second retardation layer 22 are resin films. The first retardation layer 21 and the second retardation layer 22 are laminated via the first adhesive layer 31. In addition, the second adhesive layer 32 is laminated on the surface of the second retardation layer 22 that is not in contact with the first adhesive layer 31. Typically, the second adhesive layer 32 is attached to a component of an image display panel such as a reflector via the second adhesive layer 32. The storage modulus G' of the second adhesive layer AD2 exceeds 0.15 MPa. When the retardation layer-attached polarizing plate 100 is placed in a heating environment, the polarizer 11 and the second retardation layer 22 may undergo dimensional changes. When arranged in an image display device, the second retardation layer 22 may be fixed to a reflector. As a result, stress due to dimensional changes may easily accumulate in the second retardation layer. When dimensional changes occur in the retardation layer, the optical characteristics may change and the image display performance may deteriorate. For this reason, a retardation layer-attached polarizing plate having superior durability is required. As described above, the retardation layer-attached polarizing plate of the embodiment of the present invention has a storage elastic modulus G' of the pressure-sensitive adhesive layer (more specifically, the pressure-sensitive adhesive forming the pressure-sensitive adhesive layer) as the second pressure-sensitive adhesive layer. AD2is more than 0.15 MPa. By using such a pressure-sensitive adhesive layer and a resin film as the first retardation layer, the dimensional change of the polarizer and the second retardation layer can be suppressed. As a result, a retardation layer-attached polarizing plate having excellent durability can be provided. In this specification, the storage modulus G' refers to a value measured by a dynamic viscoelasticity measuring device at 25°C.

[0012] The storage modulus G' of the second pressure-sensitive adhesive layer AD2 and the storage modulus G' of the first pressure-sensitive adhesive layer AD1 is preferably G' AD2 >G' AD1 The storage modulus G' of the second pressure-sensitive adhesive layer satisfies the relationship: AD2 and the storage modulus G' of the first pressure-sensitive adhesive layer AD1 If the relationship between the thickness and the thickness of the polarizer is as described above, the stress caused by the dimensional change of the polarizer can be suppressed from being transmitted to the second retardation layer. Also, the dimensional change of the second retardation layer itself can be suppressed. As a result, a retardation layer polarizing plate having excellent durability can be provided.

[0013] Storage modulus G' of the second adhesive layer AD2 and the storage modulus G' of the first pressure-sensitive adhesive layer AD1 Difference from (G' AD2 -G' AD1 The storage modulus G' of the second pressure-sensitive adhesive layer is preferably 0.0 MPa to 2.0 MPa, more preferably 0.02 MPa to 1.5 MPa, and further preferably 0.06 MPa to 1.0 MPa. AD2 and the storage modulus G' of the first pressure-sensitive adhesive layer AD1 Difference from (G' AD2 -G' AD1 ) in the above range, the stress caused by the dimensional change of the polarizer can be suppressed from being applied to the second retardation layer. In addition, the dimensional change of the second retardation layer itself can also be suppressed. As a result, a retardation layer polarizing plate having excellent durability can be provided.

[0014] As described above, the retardation layer-attached polarizing plate 100 can be attached to an image display panel included in an image display device, for example, via the second adhesive layer 32. In practice, a release liner is attached to the surface of the second adhesive layer 32. The release liner can be temporarily attached until the retardation layer-attached polarizing plate is used. By using the release liner, for example, the adhesive layer 40 is protected and the retardation layer-attached polarizing plate 100 can be formed into a roll.

[0015] The retardation layer-attached polarizing plate 100 may further have other functional layers not shown. The type, characteristics, number, combination, arrangement, etc. of the other functional layers that the retardation layer-attached polarizing plate may have may be appropriately set according to the purpose. For example, the retardation layer-attached polarizing plate may further have a conductive layer or a conductive layer-attached isotropic substrate. A retardation layer-attached polarizing plate having a conductive layer or a conductive layer-attached isotropic substrate is applied to, for example, a so-called inner touch panel type input display device in which a touch sensor is incorporated inside an image display panel. As another example, the retardation layer-attached polarizing plate may further have other retardation layers. The optical characteristics (e.g., refractive index characteristics, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement, etc. of the other retardation layers may be appropriately set according to the purpose. As a specific example, the viewing side of the polarizer may be provided with other retardation layers (typically, a layer that imparts (elliptical) polarizing function, a layer that imparts ultra-high retardation) that improve visibility when viewed through polarized sunglasses. By providing such a layer, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses, and the present invention can be suitably applied to image display devices that can be used outdoors.

[0016] Each member constituting the retardation layer-attached polarizing plate 100 is typically laminated via any suitable adhesive layer. Specific examples of the adhesive layer include an adhesive layer and a pressure-sensitive adhesive layer. Although not shown, the protective layer 12 is attached to the polarizer 11 via an adhesive layer (preferably using an active energy ray-curable adhesive), for example. In addition, for example, the polarizing plate 10 and the first retardation layer 21 can be laminated via an adhesive layer (preferably using an active energy ray-curable adhesive) or via a pressure-sensitive adhesive layer (preferably using an acrylic pressure-sensitive adhesive). The thickness of the adhesive layer is, for example, 0.1 μm or more, preferably 0.3 μm to 5 μm, and more preferably 0.5 μm to 3 μm. The thickness of the pressure-sensitive adhesive layer is, for example, 3 μm or more, preferably 5 μm to 100 μm, and more preferably 10 μm to 50 μm.

[0017] The total thickness of the retardation layer-attached polarizing plate is, for example, 150 μm or less, preferably 100 μm or less, and for example, 30 μm or more, preferably 60 μm or more. The total thickness of the retardation layer-attached polarizing plate refers to the total thickness of the polarizing plate, the first retardation layer and the second retardation layer, the first adhesive layer and the second adhesive layer, and the adhesive layer for laminating them (that is, the total thickness of the retardation layer-attached polarizing plate does not include the thickness of the release liner that may be temporarily attached to the surface of the second adhesive layer).

[0018] The retardation layer-attached polarizing plate 100 may be in the form of a sheet or a long sheet. In this specification, the term "long sheet" means a long and narrow shape whose length is sufficiently longer than its width, and includes, for example, a long and narrow shape whose length is 10 times or more, preferably 20 times or more, than its width. The long laminate can be wound into a roll.

[0019] B. Polarizing plate The polarizing plate 10 includes a polarizer 11. The polarizing plate preferably further includes a protective layer 12 on the side of the polarizer 11 opposite to the side on which the first retardation layer 21 is arranged. If necessary, the polarizing plate 10 may include a protective layer on the side of the polarizer 11 on which the first retardation layer 21 is arranged.

[0020] B-1.Polarizer The polarizer 11 is typically a resin film containing a dichroic material (e.g., iodine). Examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA)-based films, partially formalized PVA-based films, and partially saponified ethylene-vinyl acetate copolymer-based films.

[0021] The thickness of the polarizer is, for example, 18 μm or less, preferably 15 μm or less, more preferably 12 μm or less, and further preferably 8 μm or less. The thickness of the polarizer is preferably 1 μm or more.

[0022] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 40.0% to 46.0%, preferably 41.0% to 45.0%, and more preferably 41.5% to 44.5%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0023] The polarizer may be produced by any appropriate method. Specifically, the polarizer may be produced from a single-layer resin film or may be produced by using a laminate including a substrate.

[0024] A method for producing a polarizer from the above-mentioned single-layer resin film typically includes subjecting the resin film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, and a stretching treatment. As the resin film, for example, a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film, a partially formalized PVA film, or an ethylene-vinyl acetate copolymer partially saponified film is used. The method may further include an insolubilization treatment, a swelling treatment, a crosslinking treatment, etc. Such a production method is well known and commonly used in the art, so a detailed description thereof will be omitted.

[0025] The polarizer obtained by using the laminate containing the above-mentioned substrate can be produced, for example, by using a laminate of a resin substrate and a resin film or resin layer (typically, a PVA-based resin layer). Specifically, the polarizer can be produced by applying a PVA-based resin solution to a resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, preferably, a PVA-based resin layer containing a halide and a PVA-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, preferably, the laminate is subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of the present embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and high optical properties can be achieved. In addition, by simultaneously increasing the orientation of PVA in advance, problems such as a decrease in the orientation of PVA and dissolution can be prevented when immersed in water in the subsequent dyeing and stretching steps, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in the orientation of the PVA molecules can be suppressed compared to when the PVA-based resin layer does not contain a halide, and high optical properties can be achieved. Furthermore, by shrinking the laminate in the width direction by the drying shrinkage treatment, high optical properties can be achieved. A polarizing plate can be obtained by laminating a protective layer on the peeled surface obtained by peeling the resin substrate from the obtained resin substrate / polarizer laminate, or on the surface opposite to the peeled surface. Details of such a method for producing a polarizer are described in, for example, JP 2012-73580 A and Japanese Patent No. 6470455. The entire disclosures of these publications are incorporated herein by reference.

[0026] B-2.Protective layer The protective layer 12 may be formed of, for example, any appropriate resin film that can be used as a protective layer for a polarizer. Specific examples of the resin that is the main component of the resin film include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based resins, polyvinyl alcohol-based resins, polycarbonate-based resins, polyamide-based resins, polyimide-based resins, polyethersulfone-based resins, polysulfone-based resins, polystyrene-based resins, cycloolefin-based resins such as polynorbornene, polyolefin-based resins, (meth)acrylic resins, and acetate-based resins.

[0027] The retardation layer-attached polarizing plate 100 is typically disposed on the viewing side of an image display device, and the protective layer 12 is disposed on the viewing side. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coat (HC) treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary.

[0028] The thickness of the protective layer is, for example, 5 μm to 80 μm, preferably 10 μm to 50 μm, and more preferably 15 μm to 35 μm. In addition, when the above-mentioned surface treatment is performed, the thickness of the protective layer includes the thickness of the surface treatment layer.

[0029] C. Retardation layer C-1. First retardation layer The first retardation layer 21 is a so-called positive C plate whose refractive index characteristic shows the relationship nz>nx=ny. If a positive C plate is arranged between the polarizer and the second retardation layer whose refractive index characteristic shows the relationship nx>ny≧nz, it is possible to prevent reflection in an oblique direction very well, and it is possible to further widen the viewing angle of the anti-reflection function. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the first retardation layer can be less than 10 nm.

[0030] The retardation Rth(550) in the thickness direction of the first retardation layer is preferably −70 nm to −165 nm, more preferably −80 nm to −155 nm, further preferably −90 nm to −145 nm, and particularly preferably −100 nm to −135 nm.

[0031] The first retardation layer preferably has a puncture elastic modulus of 50 g / mm or more, more preferably 52 g / mm or more, and further preferably 55 g / mm or more. The puncture elastic modulus of the first retardation layer is, for example, 200 g / mm or less. If the puncture elastic modulus of the first retardation layer is within the above range, the dimensional change of the second retardation layer (for example, expansion, contraction, etc. of the second retardation layer composed of a stretched film of a resin film) can be suitably suppressed. In this specification, the puncture elastic modulus refers to a value obtained by dividing the force (g) just before the retardation film breaks (or tears) when a needle (puncture tool) is pierced perpendicularly to the main surface of the retardation film (for example, the first retardation layer) by the strain (mm) at that time. As the needle, one with a tip diameter of 1 mmφ and 0.5R can be used. The needle piercing speed can be 0.33 cm / sec. The puncture modulus can be measured by sandwiching the retardation film between two plates with a circular hole having a diameter of 15 mm or less (for example, a diameter of 11 mm) through which a needle can pass. The puncture modulus can be measured in an environment at a temperature of 23°C. For example, the puncture modulus can be measured for five retardation films, and the average value can be used as the puncture modulus of the retardation film. Commercially available devices can be used to measure the puncture modulus. Examples of commercially available devices include a handy compression tester "KES-G5 Needle Penetration Force Measurement Specification" manufactured by Kato Tech Co., Ltd. and a small tabletop tester "EZ Test" manufactured by Shimadzu Corporation.

[0032] As described above, the first retardation layer is made of a resin film. The retardation layer can be roughly divided into an alignment layer of a liquid crystal compound (liquid crystal alignment layer) and a resin film depending on the material of the layer. If the first retardation layer adjacent to the polarizing plate is a liquid crystal alignment layer, the polarizer may be deteriorated due to the influence of the liquid crystal compound, polymerization initiator, etc. contained in the liquid crystal alignment layer. On the other hand, if the first retardation layer is a resin film, such deterioration of the polarizer can be suitably prevented.

[0033] Representative examples of the material of the resin film constituting the first retardation layer include resin materials having negative birefringence. A resin having negative birefringence is a resin that exhibits a property that the refractive index in the direction perpendicular to the stretching direction becomes maximum when uniaxially stretched. Examples of resins having negative birefringence include resins having a chemical bond or functional group with large polarization anisotropy, such as an aromatic ring or a carbonyl group, introduced into the side chain. Specific examples of resins having negative birefringence include acrylic resins, styrene resins, maleimide resins, modified polyolefin resins, and fumaric acid ester resins. The above resin materials can be used alone or in combination of two or more.

[0034] The acrylic resin can be obtained, for example, by addition polymerization of an acrylate monomer. Examples of the acrylic resin include polymethyl methacrylate (PMMA), polybutyl methacrylate, and polycyclohexyl methacrylate.

[0035] The styrene resin can be obtained, for example, by addition polymerization of a styrene monomer, such as styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, p-chlorostyrene, p-nitrostyrene, p-aminostyrene, p-carboxystyrene, p-phenylstyrene, 2,5-dichlorostyrene, and pt-butylstyrene.

[0036] The maleimide resin can be obtained, for example, by addition polymerization of a maleimide monomer. Examples of maleimide monomers include N-ethylmaleimide, N-cyclohexylmaleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-propylphenyl)maleimide, N-(2-isopropylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2,6-dipropylphenyl)maleimide, N-(2,6-diisopropylphenyl)maleimide, N-(2-methyl-6-ethylphenyl)maleimide, N-(2-chlorophenyl)maleimide, N-(2,6-dichlorophenyl)maleimide, N-(2-bromophenyl)maleimide, N-(2,6-dibromophenyl)maleimide, N-(2-biphenyl)maleimide, and N-(2-cyanophenyl)maleimide. The maleimide monomer can be obtained, for example, from Tokyo Chemical Industry Co., Ltd.

[0037] In the above-mentioned addition polymerization, the birefringence characteristics of the resulting resin can be controlled by, for example, substituting the side chains after polymerization, or by carrying out a maleimidization or grafting reaction.

[0038] The resin having negative birefringence may be copolymerized with other monomers. By copolymerizing other monomers, brittleness, moldability, and heat resistance can be improved. Examples of the other monomers include olefins such as ethylene, propylene, 1-butene, 1,3-butadiene, 2-methyl-1-butene, 2-methyl-1-pentene, and 1-hexene; acrylonitrile; (meth)acrylates such as methyl acrylate and methyl methacrylate; maleic anhydride; and vinyl esters such as vinyl acetate.

[0039] When the resin having negative birefringence is a copolymer of the styrene monomer and the other monomer, the blending ratio of the styrene monomer is preferably 50 mol% to 80 mol%. When the resin having negative birefringence is a copolymer of the maleimide monomer and the other monomer, the blending ratio of the maleimide monomer is preferably 2 mol% to 50 mol%. By blending in such a range, a resin film having excellent toughness and moldability can be obtained.

[0040] As the resin having the negative birefringence, preferably, styrene-maleic anhydride copolymer, styrene-acrylonitrile copolymer, styrene-(meth)acrylate copolymer, styrene-maleimide copolymer, vinyl ester-maleimide copolymer, olefin-maleimide copolymer, etc. are used. These can be used alone or in combination of two or more. These resins exhibit high negative birefringence and can have excellent heat resistance. These resins can be obtained, for example, from Nova Chemical Japan, Arakawa Chemical Industries, Ltd., etc.

[0041] As the resin having negative birefringence, a polymer having a repeating unit represented by the following general formula (I) is preferably used. Such a polymer exhibits a higher negative birefringence and can have excellent heat resistance and mechanical strength. Such a polymer can be obtained, for example, by using an N-phenyl-substituted maleimide in which a phenyl group having a substituent at least at the ortho position is introduced as the N-substituent of the maleimide monomer as the starting material. [ka]

[0042] In the above general formula (I), R1 to R5 each independently represent a hydrogen atom, a halogen atom, a carboxylic acid, a carboxylate, a hydroxyl group, a nitro group, or a linear or branched alkyl or alkoxy group having 1 to 8 carbon atoms (provided that R1 and R5 are not simultaneously hydrogen atoms), R6 and R7 represent a hydrogen atom, or a linear or branched alkyl or alkoxy group having 1 to 8 carbon atoms, and n represents an integer of 2 or greater.

[0043] The resin having negative birefringence is not limited to the above, and for example, the resins having negative birefringence described in JP-T-2008-544304 and JP-T-2008-544317 can be used.

[0044] The resin film forming the first retardation layer may further contain any appropriate additive, if necessary. Specific examples of the additive include plasticizers, heat stabilizers, light stabilizers, lubricants, antioxidants, UV absorbers, flame retardants, colorants, antistatic agents, compatibilizers, crosslinking agents, thickeners, etc. The type and content of the additives may be appropriately set depending on the purpose. The content of the additives in the resin film is, for example, about 3% by weight to 10% by weight.

[0045] Any suitable manufacturing method can be used as a manufacturing method for the first retardation layer composed of the resin film. In one embodiment, the resin film containing the resin material can be used as the first retardation layer as it is after film formation (i.e., in a non-stretched state). For example, when a film is formed by a solution film-forming method using a resin solution containing the resin material, stress occurs due to volume shrinkage when the resin solution is dried on a support, and the molecular chains of the polymer tend to be oriented in the in-plane direction. Therefore, when a resin material having high birefringence expression and negative intrinsic birefringence is used, a coating film having large thickness direction birefringence can be formed on a support by shrinkage action during drying, and the coating film can be used as a positive C plate as it is.

[0046] The thickness of the first retardation layer is, for example, from 1 μm to 40 μm, preferably from 3 μm to 35 μm, more preferably from 5 μm to 30 μm.

[0047] C-2. Second retardation layer The second retardation layer 22 exhibits a refractive index characteristic of nx > ny ≧ nz. In one embodiment, the second retardation layer can function as a λ / 4 plate. The in-plane retardation Re(550) of the second retardation layer is, for example, from 120 nm to 170 nm, preferably from 130 nm to 160 nm, more preferably from 140 nm to 150 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. In this specification, a retardation layer having a refractive index characteristic of nx > ny = nz may be referred to as a positive A plate, and a retardation layer having a refractive index characteristic of nx > ny > nz may be referred to as a negative B plate.

[0048] The Nz coefficient of the second retardation layer is preferably from 0.9 to 3, more preferably from 0.9 to 2.5, still more preferably from 0.9 to 1.5, and particularly preferably from 0.9 to 1.3. By satisfying such a relationship, when the polarizing plate with a retardation layer obtained is used in an image display device, an extremely excellent reflection color phase can be achieved.

[0049] The second retardation layer is arranged such that its slow axis forms an angle of, for example, 40° to 50° or 130° to 140°, preferably 42° to 48° or 132° to 138°, more preferably about 45° or about 135° with the absorption axis of the polarizer 12. By adopting such a configuration, a polarizing plate with a retardation layer having extremely excellent circular polarization characteristics (as a result, extremely excellent antireflection characteristics) can be obtained.

[0050] The second retardation layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the retardation value hardly changes according to the wavelength of the measurement light. In one embodiment, the second retardation layer exhibits an inverse dispersion wavelength characteristic. In this case, Re(450) / Re(550) of the retardation layer is, for example, 0.8 or more and less than 1, and preferably 0.8 or more and 0.95 or less. With such a configuration, it is possible to realize very excellent antireflection properties.

[0051] The second retardation layer is a resin film, and is preferably a stretched resin film.

[0052] In one embodiment, the second retardation layer preferably has an absolute value of a photoelastic coefficient of 2×10 -11 m 2 / N or less, preferably 2.0×10 -13 m 2 / N~1.5×10 -11 m 2 / N, and more preferably 1.0×10 -12 m 2 / N~1.2×10 -11 m 2 If the absolute value of the photoelastic coefficient is within this range, the retardation is unlikely to change even when shrinkage stress occurs during heating. As a result, the thermal unevenness of the resulting image display device can be effectively prevented.

[0053] Examples of the resin contained in the resin film include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination (for example, blended or copolymerized). When the second retardation layer exhibits reverse dispersion wavelength characteristics, a resin film containing a polycarbonate-based resin or a polyester carbonate-based resin (hereinafter, sometimes simply referred to as a polycarbonate-based resin) may be suitably used.

[0054] As the polycarbonate-based resin, any suitable polycarbonate-based resin can be used as long as the effects of the present invention can be obtained. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of an alicyclic diol, an alicyclic dimethanol, a di-, tri- or polyethylene glycol, and an alkylene glycol or a spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol, and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used for the second retardation layer and methods for forming the second retardation layer are described, for example, in JP-A-2014-10291, JP-A-2014-26266, JP-A-2015-212816, JP-A-2015-212817, and JP-A-2015-212818, and the descriptions in these publications are incorporated herein by reference.

[0055] The thickness of the second retardation layer is preferably 100 μm or less. Specifically, the thickness of the second retardation layer formed of a stretched resin film is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, more preferably 10 μm to 60 μm, and further preferably 20 μm to 50 μm.

[0056] D.Adhesive layer As described above, the storage modulus G' of the second pressure-sensitive adhesive layer AD2 The storage modulus G' of the second pressure-sensitive adhesive layer is greater than 0.15 MPa.AD2 and the storage modulus G' of the first pressure-sensitive adhesive layer AD1 is preferably G' AD2 >G' AD1 The storage modulus G' of the second pressure-sensitive adhesive layer satisfies the relationship: AD2 and the storage modulus G' of the first pressure-sensitive adhesive layer AD1 If the relationship between the thickness and the thickness of the polarizer is as described above, the stress caused by the dimensional change of the polarizer can be suppressed from being applied to the second retardation layer. Also, the dimensional change of the second retardation layer itself can be suppressed. As a result, a retardation layer polarizing plate having excellent durability can be provided.

[0057] D-1. First adhesive layer The first adhesive layer 31 is disposed between the first retardation layer 21 and the second retardation layer 22. The first adhesive layer may be formed of any appropriate adhesive. For example, specific examples of adhesives constituting the adhesive layer include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, and the like, an adhesive having desired properties according to the purpose can be prepared. The base resin of the adhesive may be one type only, or two or more types may be used in combination. The first adhesive layer and the second adhesive layer may be formed of the same adhesive, or may be formed of different adhesives. From the viewpoints of transparency, processability, durability, and the like, an acrylic adhesive (acrylic adhesive composition) is preferable.

[0058] The acrylic pressure-sensitive adhesive typically contains a (meth)acrylic polymer as a main component, and the (meth)acrylic polymer may be contained in the pressure-sensitive adhesive in an amount of, for example, 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more of the solid content of the pressure-sensitive adhesive.

[0059] The (meth)acrylic polymer contains alkyl (meth)acrylate as a main component as a monomer unit. Here, (meth)acrylate refers to acrylate and / or methacrylate. The alkyl (meth)acrylate may be contained in a proportion of preferably 80% by weight or more, more preferably 90% by weight or more, in the monomer components forming the (meth)acrylic polymer. Examples of the alkyl group of the alkyl (meth)acrylate include linear or branched alkyl groups having 1 to 18 carbon atoms. The average carbon number of the alkyl group is preferably 3 to 9, more preferably 3 to 6.

[0060] The acrylic adhesive may preferably contain a silane coupling agent and / or a crosslinking agent. Examples of the silane coupling agent include an epoxy group-containing silane coupling agent. Examples of the crosslinking agent include an isocyanate-based crosslinking agent and a peroxide-based crosslinking agent. Furthermore, the acrylic adhesive composition may contain an antioxidant and / or a conductive agent. Details of the adhesive layer or the acrylic adhesive composition are described in, for example, JP 2006-183022 A, JP 2015-199942 A, JP 2018-053114 A, JP 2016-190996 A, and WO 2018 / 008712 A, and the descriptions in these publications are incorporated herein by reference.

[0061] Storage modulus G' of the first pressure-sensitive adhesive layer AD1 (i.e., the storage modulus of the pressure-sensitive adhesive forming the first pressure-sensitive adhesive layer) can be adjusted to any appropriate value. AD1 is preferably 0.05 MPa to 0.14 MPa, more preferably 0.06 MPa to 0.13 MPa, and further preferably 0.07 MPa to 0.12 MPa. When the storage modulus of the first pressure-sensitive adhesive layer is within the above range, the stress caused by the dimensional change of the polarizer is prevented from being transmitted to the second retardation layer, and a retardation-layer-attached polarizing plate having excellent durability can be provided.

[0062] The thickness of the first pressure-sensitive adhesive layer can be set to any appropriate value. The thickness of the first pressure-sensitive adhesive layer is preferably 2 μm to 25 μm, more preferably 3 μm to 20 μm, and even more preferably 5 μm to 15 μm. When the thickness of the first pressure-sensitive adhesive layer is within the above range, the adhesion between the first retardation layer and the second retardation layer can be ensured. In addition, the transmission of stress due to dimensional changes in the polarizer to the second retardation layer can be further suppressed.

[0063] D-2. Second adhesive layer Storage modulus G' of the second adhesive layer AD2 (i.e., the storage modulus of the pressure-sensitive adhesive forming the second pressure-sensitive adhesive layer) can be adjusted to any appropriate value. AD2 The storage modulus G' of the second pressure-sensitive adhesive layer is preferably greater than 0.15 MPa, is preferably 0.16 MPa to 2.0 MPa, and is more preferably 0.17 MPa to 1.0 MPa. AD2 When the thickness is in the above range, the dimensional change of the second retardation layer is suppressed, and a retardation layer-attached polarizing plate having excellent durability can be provided.

[0064] The thickness of the second pressure-sensitive adhesive layer can be set to any appropriate value. The thickness of the second pressure-sensitive adhesive layer is preferably 10 μm to 40 μm, more preferably 12 μm to 35 μm, and further preferably 15 μm to 25 μm. When the thickness of the second pressure-sensitive adhesive layer is within the above range, the adhesion between the retardation layer-attached polarizing plate and the image display panel can be ensured. In addition, dimensional change of the second retardation layer is suppressed, and a retardation layer-attached polarizing plate with excellent durability can be provided.

[0065] The second adhesive layer has a storage modulus G' AD2 The second adhesive layer may be formed by any suitable adhesive, as long as the compressive strength exceeds 0.15 MPa. For example, the adhesives exemplified above may be used. In one embodiment, the second adhesive layer is formed by using an adhesive composition containing, as monomer units, acrylic acid, a (meth)acrylic polymer containing an alkyl (meth)acrylate and an aromatic ring-containing monomer, and a polyether compound having a reactive silyl group.

[0066] The aromatic ring-containing monomer refers to a compound that contains an aromatic group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the aromatic group include a benzene ring, a naphthalene ring, a biphenyl ring, and a heterocycle. Examples of the heterocycle include a morpholine ring, a piperidine ring, a pyrrolidine ring, and a piperazine ring. Examples of such compounds include (meth)acrylates containing an aromatic group. Only one type of aromatic ring-containing monomer may be used, or two or more types may be used in combination.

[0067] Specific examples of the (meth)acrylate containing an aromatic group include, for example, benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, ethylene oxide modified cresol (meth)acrylate, phenol ethylene oxide modified (meth)acrylate, 2- Examples of the (meth)acrylates containing a benzene ring include hydroxy-3-phenoxypropyl (meth)acrylate, methoxybenzyl (meth)acrylate, chlorobenzyl (meth)acrylate, cresyl (meth)acrylate, and polystyryl (meth)acrylate; those containing a naphthalene ring include hydroxyethylated β-naphthol acrylate, 2-naphthoethyl (meth)acrylate, 2-naphthoxyethyl acrylate, and 2-(4-methoxy-1-naphthoxy)ethyl (meth)acrylate; and those containing a biphenyl ring include biphenyl (meth)acrylate. Examples of (meth)acrylates containing a heterocycle include thiol (meth)acrylate, pyridyl (meth)acrylate, and pyrrole (meth)acrylate. Other examples of (meth)acrylic monomers containing a heterocycle include N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine.

[0068] Specific examples of vinyl compounds containing an aromatic group include vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinylcarboxylic acid amides, styrene, and α-methylstyrene.

[0069] The aromatic ring-containing monomer may contain a functional group such as sulfonic acid in addition to a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the aromatic ring-containing monomer having the functional group include styrene sulfonic acid and (meth)acryloyloxynaphthalene sulfonic acid.

[0070] As the aromatic ring-containing monomer, from the viewpoint of adhesive properties and durability, (meth)acrylates containing an aromatic group are preferred, and among them, benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferred, and benzyl (meth)acrylate is more preferred.

[0071] The content of the aromatic ring-containing monomer in the (meth)acrylic polymer is preferably 1 wt % to 50 wt %, more preferably 1 wt % to 35 wt %, even more preferably 1 wt % to 20 wt %, still more preferably 7 wt % to 18 wt %, and particularly preferably 10 wt % to 16 wt %, based on 100 wt % of all constituent monomers of the (meth)acrylic polymer.

[0072] As the monomer component other than the aromatic ring-containing monomer in the (meth)acrylic polymer, any appropriate monomer can be used, for example, the above-mentioned alkyl (meth)acrylates.

[0073] As the polyether compound, any suitable compound having a polyether skeleton can be used. The polyether compound preferably has a polyether skeleton and has a group represented by the general formula: -SiR a M 3-a(wherein R is a monovalent organic group having 1 to 20 carbon atoms which may have a substituent, M is a hydroxyl group or a hydrolyzable group, and a is an integer of 1 to 3; however, when there are multiple R's, the multiple R's may be the same or different, and when there are multiple M's, the multiple M's may be the same or different).

[0074] The polyether skeleton of the polyether compound preferably has a repeating structural unit of a linear or branched oxyalkylene group having 1 to 10 carbon atoms. The structural unit of the oxyalkylene group preferably has 2 to 6 carbon atoms, more preferably 3 carbon atoms. The repeating structural unit of the oxyalkylene group may be a repeating structural unit of one type of oxyalkylene group, or may be a repeating structural unit of a block unit or random unit of two or more types of oxyalkylene groups. Examples of the oxyalkylene group include an oxyethylene group, an oxypropylene group, and an oxybutylene group. Among these oxyalkylene groups, those having a structural unit of an oxypropylene group (particularly, -CH2CH(CH3)O-) are preferred.

[0075] The polyether compound preferably has a main chain substantially composed of a polyether skeleton, in addition to the reactive silyl group. Here, the main chain substantially composed of a polyoxyalkylene chain means that it may contain a small amount of other chemical structures. The other chemical structures may include, for example, the chemical structure of an initiator when producing a repeating structural unit of an oxyalkylene group related to a polyether skeleton, and a linking group with a reactive silyl group. The repeating structural unit of an oxyalkylene group related to a polyether skeleton is preferably 50% by weight or more, more preferably 80% by weight or more, of the total weight of the polyether compound.

[0076] The polyether compound may be a commercially available product. Specific examples of the polyether compound (B) include MS Polymer S203, S303, S810 (trade names), SILYL EST250, EST280, Silyl SAT10, SAT200, SAT220, SAT350, SAT400 (trade names), manufactured by Kaneka Corporation, and EXCESTARS S2410, S2420, or S3430 (trade names), manufactured by Asahi Glass Co., Ltd.

[0077] The content of the polyether compound in the pressure-sensitive adhesive composition is preferably 0.001 to 20 parts by weight relative to 100 parts by weight of the (meth)acrylic polymer. The content of the polyether compound is more preferably 0.01 parts by weight or more, even more preferably 0.02 parts by weight or more, particularly preferably 0.1 parts by weight or more, and most preferably 0.5 parts by weight or more. The content of the polyether compound is more preferably 10 parts by weight or less, even more preferably 5 parts by weight or less, and particularly preferably 3 parts by weight or less.

[0078] A pressure-sensitive adhesive containing a (meth)acrylic polymer and a polyether compound is described, for example, in Japanese Patent No. 4959014. The disclosure of this publication is incorporated herein by reference.

[0079] E. Release Liner The release liner may be, for example, a flexible plastic film. Examples of the plastic film include a polyethylene terephthalate film, a polyethylene film, a polypropylene film, and a polyester film. The thickness of the release liner is, for example, 3 μm or more and, for example, 200 μm or less. The surface of the release liner is coated with a release agent. Specific examples of the release agent include a silicone-based release agent, a fluorine-based release agent, and a long-chain alkyl acrylate-based release agent.

[0080] F. Image display device The retardation layer-attached polarizing plate can be applied to an image display device. Therefore, an image display device according to an embodiment of the present invention includes the retardation layer-attached polarizing plate. Representative examples of the image display device include a liquid crystal display device and an electroluminescence (EL) display device (e.g., an organic EL display device, an inorganic EL display device). EXAMPLES

[0081] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. Various measurement methods are as follows. Furthermore, unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight.

[0082] (1) Thickness The thickness of 1 μm or less was measured using a scanning electron microscope (manufactured by JEOL Ltd., product name "JSM-7100F"), and the thickness of more than 1 μm was measured using a digital micrometer (manufactured by Anritsu Corporation, product name "KC-351C").

[0083] (2) In-plane retardation Re(λ) and thickness retardation Rth(λ) The in-plane retardation at each wavelength at 23°C was measured using a Mueller matrix polarimeter (Axometrics, product name "Axoscan").

[0084] (3) Refractive index The average refractive index was measured using an Abbe refractometer manufactured by Atago Co., Ltd., and the refractive indexes nx, ny, and nz were calculated from the above retardation value.

[0085] (4)Durability The retardation layer-attached polarizing plates obtained in the Examples and Comparative Examples were cut into a size of 70 mm in length and 150 mm in width to prepare samples. The samples were cut so that the slow axis direction of the second retardation layer was in the horizontal direction of the sample. The second adhesive layer of the retardation layer-attached polarizing plate was attached to a reflector (manufactured by Toray Film Processing Co., Ltd., product name "Cerapeel DMS-X42", total light reflectance: 86%), and subjected to a durability test at 80°C for 500 hours. After the durability test, the hue a value and hue b value of the sample were measured using a spectrophotometer / colorimeter "CM-26d" manufactured by Konica Minolta, and the center (a * A , b * A ) and the end of the retardation layer-attached polarizing plate (a * B , b * B ) hue difference is Δa * b * The intersection of the diagonal lines of the retardation layer-attached polarizing plate was defined as the center of the retardation layer-attached polarizing plate, and the end of the center line extending in the longitudinal direction (horizontal direction) was defined as the end of the retardation layer-attached polarizing plate. Δa * b * =√(a * A- a * B ) 2 +(b * A -b * B ) 2

[0086] (5) Storage modulus G' Measurements were performed at 25°C using a dynamic viscoelasticity device (viscoelasticity spectrometer, Rheometric Scientific, "ARES device").

[0087] [Production Example 1: Preparation of Polarizing Plate A] (Preparation of polarizer) As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating liquid) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Mitsubishi Chemical Corporation, product name "GOHSENEX Z410") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of 5 μm was formed on the resin substrate.

[0088] (Preparation of Polarizing Plate A) An HC-TAC film was attached as a protective layer to the surface of the obtained polarizer (the surface opposite to the resin substrate) via an ultraviolet-curing adhesive. Specifically, the ultraviolet-curing adhesive was applied to a thickness of 1.0 μm, and the two were attached using a rolling machine. Then, the adhesive was cured by irradiating UV rays from the protective layer side. The HC-TAC film was a film in which a hard coat (HC) layer (7 μm thick) was formed on a triacetyl cellulose (TAC) film (25 μm thick), and the TAC film was attached to the polarizer side. Next, the resin substrate was peeled off and removed to obtain a polarizing plate A having a configuration of [polarizer / TAC protective layer with HC]. The single transmittance of the polarizing plate A was 43%, and the polarization degree was 99.9%.

[0089] [Manufacturing Example 2: Preparation of positive C plate] In an autoclave equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 48 parts by weight of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical, trade name: Metolose 60SH-50), 15601 parts by weight of distilled water, 8161 parts by weight of diisopropyl fumarate, 240 parts by weight of 3-ethyl-3-oxetanylmethyl acrylate and 45 parts by weight of t-butyl peroxypivalate as a polymerization initiator were placed, and after nitrogen bubbling for 1 hour, the mixture was stirred and held at 49°C for 24 hours to carry out radical suspension polymerization. The mixture was then cooled to room temperature, and the suspension containing the generated polymer particles was centrifuged. The obtained polymer was washed twice with distilled water and twice with methanol, and then dried under reduced pressure. The obtained fumarate ester resin was dissolved in a toluene-methyl ethyl ketone mixed solution (toluene / methyl ethyl ketone, 50% by weight / 50% by weight) to prepare a 20% solution. Furthermore, 5 parts by weight of tributyl trimellitate was added as a plasticizer to 100 parts by weight of the fumaric acid ester resin to prepare a dope. A biaxially stretched film (thickness 75 μm) of polyester (polyethylene-terephthalate / isophthalate copolymer) was used as the support film. The prepared dope was applied to the support film so that the film thickness after drying was 28 μm, and dried at 140 ° C. This resulted in a resin film (positive C plate A) exhibiting a refractive index characteristic of nz > nx = ny. The thickness of the positive C plate A was 28 μm, the in-plane retardation Re (550) was ≒ 0 nm, and the thickness direction retardation Rth (550) was -135 nm.

[0090] [Manufacturing Example 3: Preparation of negative B plate] Into a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and reflux condensers controlled at 100°C, 29.60 parts by weight (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by weight (0.200 mol) of isosorbide (ISB), 42.28 parts by weight (0.139 mol) of spiroglycol (SPG), 63.77 parts by weight (0.298 mol) of diphenyl carbonate (DPC), and 1.19 x 10 calcium acetate monohydrate as a catalyst were added. -2 Weight part (6.78×10 -5mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was reduced and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure to 0.2 kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the specified power was reached, nitrogen was introduced into the reactor to restore pressure, and 100 parts by weight of the produced polyester carbonate resin were melt-kneaded with 0.7 part by mass of PMMA, which was then extruded into water and the strands were cut to obtain pellets. The obtained polyester carbonate resin (pellets) was vacuum dried at 80 ° C for 5 hours, and then a long resin film with a thickness of 135 μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250 ° C), a T-die (width 200 mm, setting temperature: 250 ° C), a chill roll (setting temperature: 120 to 130 ° C) and a winder. The obtained long resin film was stretched in the width direction by about 2.8 times at 133 ° C while adjusting so as to obtain a predetermined retardation, thereby obtaining a stretched film (negative B plate A) with a thickness of 48 μm showing a refractive index characteristic of nx>ny>nz. The Re (550) of the negative B plate A was 143 nm, the Nz coefficient was 1.1, and Re (450) / Re (550) was 0.86.

[0091] [Production Example 4: Preparation of Adhesive A] 1. Preparation of Base Polymer A monomer mixture containing 94.9 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA), and 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Next, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with ethyl acetate for 100 parts by weight of the monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the nitrogen. The liquid temperature in the flask was kept at around 55°C and a polymerization reaction was carried out for 7 hours. Then, ethyl acetate was added to the resulting reaction solution to obtain a solution of a (meth)acrylic polymer with a weight average molecular weight of 2 million, adjusted to a solid content concentration of 30%. 2. Preparation of acrylic adhesive Acrylic adhesive A was prepared by blending 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution with 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, manufactured by Tosoh Corporation, product name "Coronate L") and 0.1 parts by weight of a silane coupling agent (product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.).

[0092] [Production Example 5: Preparation of Adhesive B] Into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 74.9 parts by weight of butyl acrylate (BA), 20 parts by weight of benzyl acrylate (BzA), 5 parts by weight of acrylic acid (AA), 1 part by weight of 4-hydroxybutyl acrylate (HBA), and 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator were charged together with 100 parts of ethyl acetate, and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen. The liquid temperature in the flask was then kept at around 55°C and a polymerization reaction was carried out for 8 hours to prepare a solution of an acrylic polymer having a weight average molecular weight of 2.3 million. Acrylic adhesive B was prepared by blending 3 parts by weight of trimethylolpropane / tolylene diisocyanate adduct (manufactured by Tosoh Corporation, product name "Coronate L"), 0.2 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM403"), and 1 part by weight of a polyether compound having a reactive silyl group (manufactured by Kaneka Corporation, product name "Silyl SAT10") per 100 parts by weight of the solid content of the obtained acrylic polymer solution.

[0093] [Production Example 6: Preparation of Adhesive C] 1. Preparation of (meth)acrylic polymer A monomer mixture containing 99 parts by weight of butyl acrylate (BA) and 1 part by weight of 4-hydroxybutyl acrylate (HBA) was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a cooler. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with ethyl acetate for 100 parts by weight of the above monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen. The liquid temperature in the flask was kept at about 55°C and a polymerization reaction was carried out for 7 hours. Then, ethyl acetate was added to the resulting reaction liquid to prepare a solution of a (meth)acrylic polymer with a weight average molecular weight of 1.6 million, with a solid content concentration of 30%. 2. Preparation of acrylic adhesive C Acrylic adhesive C was prepared by blending 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution with 0.1 part by weight of an isocyanate crosslinking agent (product name: Takenate D110N, trimethylolpropane xylylene diisocyanate, manufactured by Mitsui Chemicals, Inc.), 0.3 part by weight of a peroxide crosslinking agent, benzoyl peroxide (product name: Niper BMT, manufactured by Nippon Oil & Fats Co., Ltd.), and 0.1 part by weight of a silane coupling agent (product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.).

[0094] [Production Example 7: Preparation of UV-curable adhesive A] UV-curable adhesive A was prepared by mixing 50 parts of unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone (manufactured by Daicel Corporation, product name "Placcel FA-1DDM"), 10 parts of polyethylene glycol diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Acrylate 9EG-A"), 20 parts of acryloyl morpholine, 15 parts of acrylic polymer (manufactured by Toagosei Co., Ltd., product name "ARUFON UP-1190"), 3 parts of photopolymerization initiator (manufactured by IGM Resins, product name "Omnirad 907"), and 2 parts of photopolymerization initiator (manufactured by Nippon Kayaku Co., Ltd., product name "KAYACURE-DETX-S").

[0095] [Example 1] The polarizer of the polarizing plate A was coated with ultraviolet-curing adhesive A to a thickness of 1.0 μm, and the positive C plate was attached to it. Next, adhesive A was applied to the positive C plate to form a first adhesive layer with a thickness of 15 μm, and the negative B plate was attached to it. At this time, the negative B plate was attached to it so that the slow axis direction of the negative B plate was at an angle of 45° clockwise with respect to the absorption axis direction of the polarizer. Next, adhesive B was applied to the negative C plate to form a second adhesive layer with a thickness of 15 μm, and a retardation layer-attached polarizing plate having a configuration of polarizing plate (HC-TAC / polarizer) / adhesive layer / positive C plate / first adhesive layer (adhesive A) / negative B plate / second adhesive layer (adhesive B) was obtained. A release liner was attached to the second adhesive layer until evaluation. The results are shown in Table 1.

[0096] [Example 2] A retardation layer-attached polarizing plate was obtained in the same manner as in Example 1, except that the first pressure-sensitive adhesive layer (thickness: 15 μm) was formed using the pressure-sensitive adhesive C. The results are shown in Table 1.

[0097] Comparative Example 1 A retardation layer-attached polarizing plate was obtained in the same manner as in Example 1, except that the second pressure-sensitive adhesive layer (thickness: 15 μm) was formed using the pressure-sensitive adhesive A. The results are shown in Table 1.

[0098] Comparative Example 2 A retardation layer-attached polarizing plate was obtained in the same manner as in Comparative Example 1, except that the first pressure-sensitive adhesive layer (thickness: 15 μm) was formed using pressure-sensitive adhesive B. The results are shown in Table 1.

[0099] Comparative Example 3 A retardation layer-attached polarizing plate was obtained in the same manner as in Example 1, except that the first pressure-sensitive adhesive layer (thickness: 15 μm) was formed using pressure-sensitive adhesive B. The results are shown in Table 1.

[0100] [Table 1]

[0101] As shown in Table 1, the retardation layer-attached polarizing plate of the embodiment of the present invention had reduced variation in hue and was excellent in durability. [Industrial Applicability]

[0102] The retardation layer-attached polarizing plate according to the embodiment of the present invention can be used, for example, in an image display device. Representative examples of the image display device include a liquid crystal display device, an organic EL display device, and an inorganic EL display device. [Explanation of symbols]

[0103] 10 Polarizing plate 11 Polarizer 12 Protective layer 21 First retardation layer 22 Second retardation layer 31 First adhesive layer 32 Second adhesive layer 100 Polarizing plate with retardation layer

Claims

1. A polarizing plate including a polarizer; a first retardation layer; a first pressure-sensitive adhesive layer; a second retardation layer; and a second pressure-sensitive adhesive layer, in this order; The first retardation layer has a refractive index characteristic that satisfies the relationship of nz>nx=ny, The second retardation layer has a refractive index characteristic that satisfies the relationship of nx>ny≧nz, the first retardation layer and the second retardation layer are resin films, Storage modulus G' of the second pressure-sensitive adhesive layer AD2 A polarizing plate with a retardation layer, wherein the retardation strength exceeds 0.15 MPa.

2. The polarizing plate with a retardation layer according to claim 1 , wherein the polarizer and the first retardation layer are laminated via an adhesive layer.

3. The second retardation layer has an Re(550) of 120 nm to 170 nm, 2. The polarizing plate with a retardation layer according to claim 1, wherein an angle between a slow axis of the second retardation layer and an absorption axis of the polarizer is 40° to 50° or 130° to 140°.

4. The polarizing plate with a retardation layer according to claim 1 , wherein the second retardation layer is a resin film containing a polycarbonate resin.

5. Storage modulus G' of the second pressure-sensitive adhesive layer AD2 and the storage modulus G' of the first pressure-sensitive adhesive layer AD1 And G' AD2 >G' AD1 The retardation layer-attached polarizing plate according to claim 1 , which satisfies the following relationship:

6. The retardation layer-attached polarizing plate according to claim 1 , which is used in an organic electroluminescence display device.

7. An image display device comprising the retardation layer-attached polarizing plate according to claim 1 .

8. 8. The image display device according to claim 7, which is an organic electroluminescence display device.

Citation Information

Patent Citations

  • Polarizing plate with optical compensation layer and organic el panel using the same

    JP2019066882A